Methyl oleate deoxygenation for production of diesel fuel aliphatic hydrocarbons over Pd/SBA-15 catalysts - Lee , Siew Pei (2013)
Background: Catalytic deoxygenation is a prominent process for production of renewable fuels from vegetable oil. In this work, deoxygenation of technical grade methyl oleate to diesel fuel aliphatic hydrocarbons (C15 – C18) is evaluated with several parameters including temperature, hydrogen pressure and reaction time in a stirred batch reactor over Pd/SBA-15 catalysts. Results: Two different SBA-15 morphologies i.e. spherelike and necklacelike structures have been synthesize as supports for Pd active metal. It is found that Pd dispersion on necklacelike SBA-15 is higher than that of spherelike SBA-15. Notably, higher Pd dispersion on necklacelike SBA-15 provides significant deoxygenation efficiency as compared to Pd/SBA-15-spherelike. Results show that H2 pressures greatly determine the total ester conversion and selectivity to C15 – C18 aliphatic hydrocarbons. Total ester conversions with 55% selectivity to n-heptadecane are achieved using Pd/SBA-15-necklacelike at 270°C and 60 bar H2 pressure within 6 h reaction time. Gas phase study reveals that formation of C17 is generated via indirect decarbonylation when the reaction time is prolonged. Conclusions: Pd/SBA-15-necklacelike catalyst exhibits good catalytic performance with high selectivity to diesellike aliphatic hydrocarbons (C15 – C18). The physicochemical properties of the Pd supported on different SBA-15 morphologies influence the deoxygenation activity of the catalysts. Furthermore, the reaction pathways are governed by the H2 pressure as well as reaction duration.